1986
DOI: 10.1136/bmj.293.6539.107
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of compliance with screening for colorectal cancer.

Abstract: A randomised trial of compliance with screening for colorectal cancer by means of the haemoccult test was conducted in Farnborough and Basingstoke districts. In each of the 14 participating practices (41 general practitioners) 25 852 men and women aged between 40 and 70 years were randomly allocated by household to one of six groups. The group determined the method of invitation to screening: a letter and the test were sent to the patient, or a letter with an appointment to attend the surgery was sent, or duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…Few randomised trials have been conducted to evaluate the effectiveness of intervention in increase compliance to CRCS with FOBT [15][16][17][18][19][20][21][22], and only two involved a GP reminder as intervention [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Few randomised trials have been conducted to evaluate the effectiveness of intervention in increase compliance to CRCS with FOBT [15][16][17][18][19][20][21][22], and only two involved a GP reminder as intervention [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…230 Three trials of mailed materials focusing on barriers to screening uptake reported an increase in uptake: one in FS screening 231 and two in gFOBt screening. 178,232 Two other trials observed no effect 37,233 and one saw reduced uptake with mailed materials. 234 A recent US-based study also failed to demonstrate a statistically significant increase in uptake associated with adding an educational pamphlet, video and simplified gFOBt kit instruction sheet to usual care materials.…”
Section: Comparison With Other Studiesmentioning
confidence: 96%
“…Even among some physicians there is limited appreciation of the disease and of the potential importance of a positive occult blood test [139][140][141][142]. Thus it is not surprising that success in obtaining patient cooperation varies considerably among individual physicians [143]. Although most doctors apparently agree with the American Cancer Society's guidelines for colorectal screening, only a minority actually follows them in clinical practice ]139].…”
Section: Supporting Evidencementioning
confidence: 99%
“…132,135, 146], although not all [136,143], indicate that elderly patients have the lowest compliance with occult blood testing. This is a major blow to the screening concept, since the risk of bowel cancer [101], the likelihood of a positive test [102], and the predictive value of a positive result [102] all progressively increase with age.…”
Section: Opposing Evidencementioning
confidence: 99%